2nd International Conference & Exhibition on Semiotics and Visual Communication. - Panayides, Angelos (My University, 2026)
Invited Designer participated with the poster “I made you look”. The conference accommodated the work of 25 graphic artists from Cyprus and abroad who were invited to design a poster under the theme of Culture of Seduction [the seduction of culture]